Regional differences in dietary habits of adult Croatian population - Doko-Jelinić, Jagoda (Array, 2009)
Summary: The aim of this study was to investigate the dietary habits of the adult Croatian population according to geographical regions and gender. Date was obtained from the Croatian Adult Health Survey questionnaire, carried out in six regions of Republic of Croatia (Eastern, Northern, Central, City of Zagreb, Mountainous and Coastal), with a total of 9,070 responses. Results have shown that the highest prevalence of unhealthy dietary habits was recorded in Eastern and Central regions, while Coastal region and city of Zagreb had significantly lower prevalence of unhealthy dietary habits (P<0.05). Prevalence of unhealthy dietary habits was higher in men in all regions. Women had healthier dietary habits, what was strongly expressed in Coastal and Mountainous region. This study has shown that the unhealthy dietary habits were practiced by approximately one quarter of the adult population, regardless on the region in which they resided. Regional differences in dietary habits should be taken into account in any new public health studies and interventions